Pesan Dakwah Visual tentang Muslimah di Media Sosial Line @dakwahmuslimah - Siti Zakiyah Tifany; Uwes Fatoni (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2016)
This article discusses the message of da'wah on Muslimah in the Line @ dakwahmuslimah account both the content aspect and the form format of da'wah messages. The research method used qualitative content analysis with descriptive research type of 53 messages of da'wah uploaded account Line @dakwahmuslimah in November 2015 as many as messages. Based on the research results found that there are three message categories of da'wah, namely aqidah, syari'ah and akhlak. The format of the da'wah message include posters, memes, comics and stickers. From the format of this da'wah message found variations of content and format of visual dakwah messages, namely poster on akidah, poster on syari'ah, poster on akhlak, meme on syari'ah, comics on akidah, comics on morals and stickers on akhlak. Artikel ini membahas pesan dakwah visual tentang muslimah dalam akun Line @dakwahmuslimah baik dari aspek konten maupun bentuk format pesan dakwah. Metode penelitian yang digunakan adalah analisis isi kualitatif dengan jenis penelitian deskriptif terhadap pesan-pesan dakwah yang diunggah akun Line @dakwahmuslimah pada bulan November 2015 sebanyak 53 pesan. Berdasarkan hasil penelitian ditemukan kategori pesan dakwah terdapat tiga, yaitu akidah, syari’ah dan akhlak. Adapun format pesan dakwah meliputi poster, meme, komik dan sticker. Dari format pesan dakwah ini ditemukan variasi konten dan format pesan dakwah visual, yaitu poster akidah, poster syari’ah dan poster akhlak, meme syari’ah, komik akidah, komik akhlak dan sticker akhlak.